2013
DOI: 10.1007/s10936-013-9263-5
|View full text |Cite
|
Sign up to set email alerts
|

Modality and Children’s Scope Understanding

Abstract: This study intends to shed light on the inconclusive argument pertaining to children's acquisition of logical form (LF) operation. Specifically, we examined children's interpretations of sentences with the ambiguous modal verb yinggai 'should,' like 'Xiaohua yinggai shangchuang shuijiao le', whose meanings depend on the landing sites of yinggai at LF (root interpretation: Xiaohua is obligated to go to bed now. epistemic interpretation: It is the case that Xiaohua has gone to bed.). The results of truth value j… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…In fact, it is not always easy for native speakers of a specific language to intuitively select the more prominent meaning of a globally ambiguous sentence. For instance, Liu & Lee (2014) Their experimental results from Truth Value Judgment Task showed that adult native speakers of Mandarin Chinese predominantly set the epistemic reading (72.97%) as the default interpretation. In fact, the default meaning of the global ambiguous sentences containing yinggai 'should' in an out-of-the-blue context can only be known by the support from the quantitative data.…”
Section: The Role Of Quantitative Methods In Linguisticsmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, it is not always easy for native speakers of a specific language to intuitively select the more prominent meaning of a globally ambiguous sentence. For instance, Liu & Lee (2014) Their experimental results from Truth Value Judgment Task showed that adult native speakers of Mandarin Chinese predominantly set the epistemic reading (72.97%) as the default interpretation. In fact, the default meaning of the global ambiguous sentences containing yinggai 'should' in an out-of-the-blue context can only be known by the support from the quantitative data.…”
Section: The Role Of Quantitative Methods In Linguisticsmentioning
confidence: 99%
“…This paper does not intend to provide a detailed account for why adults and children produced different patterns of judgments. One possibility is that children have limited processing capacity (see Liu & Lee (2014); Syrett & Lidz (2009);and Trueswell et al (1999) for a detailed discussion).…”
mentioning
confidence: 99%
“…( All five critical items were created based on the construction "SUBJECT + yīnggāi 'should' + VERB PHRASE+ le 'sentence final particle'," such as (5). The sentences were globally ambiguous because the modal verb yīnggāi "should" was ambiguous between a wide-scope epistemic reading, showing possibility, and a narrow-scope root reading, showing obligation (Lin, 2011(Lin, , 2012Liu & Lee, 2014). Therefore, if the participants were aware of the ambiguity, they were expected to choose choice c. Eighteen control items, such as (6), were created to examine if the participants maintained concentration and were used to decide if the data should be included for further analyses.…”
Section: Design and Materialsmentioning
confidence: 99%